2019
DOI: 10.30574/gscbps.2019.6.1.0155
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile, blood pressure and body mass index of male waste pickers in Osogbo, Nigeria

Abstract: Waste pickers are exposed to various harmful substances capable of altering many physiologic processes. The aim of this study is to determine whether waste picking can result in dyslipidemia or abnormal blood pressure. The study was carried out in Osogbo, where 30 waste pickers and another 30 age-matched males who have not been in waste disposal business that served as control group were recruited. Body Mass Index (BMI) as well as systolic and diastolic blood pressure (BP) of each participant was obtained. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…This is an indication that the exposed individuals (scavengers) were not sufficiently exposed to harmful substances that could have modulated or alter the levels of their body lipid. This observation is also consistent with the report of Olude et al [3] among rag pickers in Osogbo. Also, the moderate total cholesterol levels recorded in both exposed and non-exposed individuals could be attributed to the lower body mass index, since lower BMI correlates positively with lower total cholesterol [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is an indication that the exposed individuals (scavengers) were not sufficiently exposed to harmful substances that could have modulated or alter the levels of their body lipid. This observation is also consistent with the report of Olude et al [3] among rag pickers in Osogbo. Also, the moderate total cholesterol levels recorded in both exposed and non-exposed individuals could be attributed to the lower body mass index, since lower BMI correlates positively with lower total cholesterol [16].…”
Section: Discussionsupporting
confidence: 93%
“…The result of HDL-C showed that there was The mean value of low density lipoprotien cholesterol for exposed and non-exposed individuals, showed no significant difference (p > 0.05) from each other. This is similar with the findings of Olude et al [3], who reported no significant (p>0.05) difference between exposed subjects and non-exposed subjects. The values of LDL recorded for exposed individuals (scavengers) and non-exposed individuals (control) fell below ≥ 3.36 mmol/L, American Heart Association cut off point reported by Rinaldi et al [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation